C, 60,480 i took thiis before it easy as
Answer:
(t^2 -4) (t^2 +4)
(t-2)(t+2)(t^2+4)
Step-by-step explanation:
t^4 - 16
We can write this as the difference of squares
We know the dfference of squares is
(a^2 - b^2) = (a-b) (a+b)
( t^2 ^2 - 4^2) = (t^2 -4) (t^2 +4)
We can write t^2 -4 as the difference of squares
t^2 -4 = t^2 -2^2 = (t-2)(t+2)
Replacing this in
( t^2 ^2 - 4^2) = (t^2 -4) (t^2 +4) = (t-2)(t+2)(t^2+4)
Answer: 15
Step-by-step explanation:
I am assuming the equation is set up like this:
(x+9)/3 = 8
Multipy by 3 to both sides
x + 9 = 24
Subtract 9
x = 15